Stoneflies left over from a mining disaster: new species and records of Perlidae (Plecoptera) from the Doce River basin, southeastern Brazil - Castillo-Velásquez, R.m.; Gonçalves, M.c.; Correia, M.c. Dias; Viana, A.d.l.; Rippel, M.l.s.; Bonfá-Neto, P.; Sperber, C.f.; Salles, F.f. (Zootaxa, 2023)
Seven years after a mudflow reached an important area of the Doce River basin, southeastern Brazil, and with the objective of reporting the current Plecoptera fauna, specimens of Anacroneuria Klapálek, 1909 (Plecoptera: Perlidae) were studied. Three new records from this basin are included: A. mineira Novaes & Bispo, 2014; A. atrifrons Klapálek, 1922; and Anacroneuria itatiaiensis Baldin, Bispo & Novaes, 2013. A new species is described: A. piranga sp. nov. Castillo-Velásquez, Gonçalves & Salles. The new species is morphologically similar to A. annulicauda Stark & Kondratieff, 2004 and A. atrifrons, but can be distinguished by the keel of the penial armature, which is flat and pointed at the apex. In addition to its description, photographs of all species are included, as well as a detailed description of the habitat of the new species.